2018
DOI: 10.3389/fphys.2018.00135
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sirt6 in Obesity and Diabetes

Abstract: Sirt6 is one of the sirtuin family members, a kind of NAD+-dependent histone deacetylase and ADP-ribose transferase enzyme. It has an important role in physiological and pathological processes, regulating aging, cancer, obesity, insulin resistance, inflammation, and energy metabolism. Recent studies have suggested that reduced Sirt6 action is related to obesity and diabetes. Aging and overnutrition, two major risk factors for obesity and diabetes, lead to decreased Sirt6 level and function, which results in ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(92 citation statements)
references
References 82 publications
(165 reference statements)
0
92
0
Order By: Relevance
“…SIRT6 plays an important role in glucose production and metabolism [46]. SIRT6 affects both gluconeogenesis and glycolysis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 plays an important role in glucose production and metabolism [46]. SIRT6 affects both gluconeogenesis and glycolysis [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Sirt6 functions as a transcriptional repressor by deacetylating the histones H3K9 and H3K56 on the promoters of multiple genes (41). Sirt6 also deacetylated nonhistone proteins such as general control nonrepressed protein 5 and forkhead box O1 and O3 (14).…”
Section: Sirt6 Regulates Ketogenesismentioning
confidence: 99%
“…SIRT2 has been linked with regulation of the activity of some Ras proteins via control of the deacylation of an internal lysine side chain . It is notable that some sirtuins, such as SIRT6, are associated with disorders in lipid and fat metabolism such as steatosis …”
Section: Is Reversal Of Intrinsic Lipidation Mediated By Deacylases Amentioning
confidence: 99%
“…[26,27] It is notable that some sirtuins, such as SIRT6, are associated with disorders in lipid and fat metabolism such as steatosis. [28] With the increasing availability of simultaneous inhibitors for multiple classes of sirtuin (pan-inhibitors), [18,29,30] it should be possible to probe the hypothesis that they are involved in reversing lysine modification by intrinsic lipidation by examining the downstream effects of sirtuin inhibition on the accumulation of proteins modified at internal lysines. This would complement experiments where reduced sirtuin activity has been shown to lead to hyperacetylation of histone proteins.…”
Section: Is Reversal Of Intrinsic Lipidation Mediated By Deacylases Amentioning
confidence: 99%